Design e imagem de marca: um estudo sobre a embalagem como elemento na construção de imagem de marca de cerveja - Strehlau, Vivian Iara (2003)
This dissertation studies packaging as an element to build brand image. It presents a theoretical review about Brand and Image; Design and Packaging” and “Beer”. Beer managers were interviewed for a qualitative research and consumers were interviewed for a quantitative survey. Consumer perception was analyzed in terms of involvement and attitude (hedonic / utilitarian). 484 questionnaires were analyzed with MANOVA. The main finding is that involvement is an important factor in packaging’s consumer perception, while attitude is almost irrelevant.